Answer:
Explanation:
some rules of logarithmic function
![ln(a) - ln(b)=ln((a)/(b))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ncxb2q2wuwhotxw3gqujpievg90rxstxe6.png)
![e^(ln(a))=a](https://img.qammunity.org/2021/formulas/mathematics/middle-school/884ivnxjsqd2hg4n2rhklfoy1knagf73ru.png)
vice-versa
![nln(a)=ln(a)^(n)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/reb75oqfc3xpp282oymgezirl9z9b86sg4.png)
If ㏑(a) = ㏑(b), then a = b
∴
![2ln(e^(ln(2x)))-ln(e^(ln(10x)))=ln(30)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u11sa7hekrqlixh0r3z8cxtv7xhcu3p2bl.png)
Use the 2nd rule to simplify it
![e^(ln(2x))=2x\\e^(ln(10x))=10x\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/axpav0ojds8sff5cgnca5wop626cwehncg.png)
2㏑(2x) - ㏑(10x) = ㏑(30)
Use the 3rd rule in the 1st term
∵ 2㏑(2x) = ㏑(2x)² = ㏑(4x²)
∴ ㏑(4x²) - ㏑(10x) = ㏑(30)
- Use the 1st rule with the left hand side
![ln(4x^(2))-ln(10x)=ln((4x^(2))/(10x))\\\\ln((4x^(2))/(10x))=ln(30)\\\\ (4x^(2))/(10x)=(2x)/(5)=(2)/(5)x\\\\ ln((2)/(5)x)=ln(30)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fptahk5bxs3eohqbg3pkjc2gst9k1c5jfj.png)
Use the 4th rule
![(2)/(5) x = 30](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ttebja5sre59c55u4q3o17jkq14h8a69wt.png)
Multiply both sides by 5
∴ 2 x = 150
- Divide both sides by 2
∴ x = 75
The value of x = 75